Answer:
![(g \circ f)(x)=9\text{x}^2-36\text{x}+50\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/tu3skddrn2wlxjvf913gbk2txjx32qryrw.png)
=====================================================
Step-by-step explanation:
The notation (g∘f)(x) is the same as g(f(x))
We'll start with the outer function g(x). Then replace each x with f(x). Afterward plug in f(x) = -3x+5 for the right hand side only.
This is what the steps look like
![g(\text{x})=\text{x}^2+2\text{x}+15\\\\g(f(\text{x}))=(f(\text{x}))^2+2f(\text{x})+15\\\\g(f(\text{x}))=(-3\text{x}+5)^2+2(-3\text{x}+5)+15\\\\g(f(\text{x}))=9\text{x}^2-30\text{x}+25-6\text{x}+10+15\\\\g(f(\text{x}))=9\text{x}^2-36\text{x}+50\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/yqg1tvtvar0vqyqu02pd735a59oi4c7l3u.png)
Therefore,
![(g \circ f)(x)=9\text{x}^2-36\text{x}+50\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/tu3skddrn2wlxjvf913gbk2txjx32qryrw.png)
You can use tools like WolframAlpha, GeoGebra, and Desmos as ways to confirm the answer.